PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN DAN BELANJA PEGAWAI TERHADAP BELANJA MODAL (Studi Empiris pada Pemerintah Kabupaten/Kota di Provinsi Nusa Tenggara Timur) - Ardiani Ika Sulistyawati; Nugrah Septiyani Purwanti (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2021)
This study aims to analyze the influence of the variables of Local Own Revenue, General Allocation Funds, Special Allocation Funds, Profit Sharing Funds and Employee Expenditures on Capital Expenditures at Regency / City Governments in East Nusa Tenggara Province 2015-2018 partially and simultaneously. The population in this study were 22 regencies / municipalities in East Nusa Tenggara Province during the 2015-2018 period. This study uses secondary data in the form of the East Nusa Tenggara Provincial Government Budget Realization Report. Hypothesis testing in this study using multiple linear regression with t test, F test and coefficient of determination. The data that has been collected is analyzed first with a classical assumption test before testing the hypothesis. The results of the study partially show that the variables of Local Own Revenue and Special Allocation Funds have a significant effect on Capital Expenditures, while the variables of General Allocation Funds, Profit Sharing Funds and Employee Expenditures have no significant effect on Capital Expenditures. The results of the research simultaneously show that the variables of Local Own Revenue, General Allocation Fund, Special Allocation Fund, Profit Sharing Fund and Employee Expenditure have an effect on capital expenditure.